Resource and capability expansion through M&A : How acquirers fill in their resource gaps in the technology sector - Mäntylä, Melisa (My University, 2022)
This study examines how acquirers expand their technological resources and capabilities through acquisitions. Even though companies have been using mergers and acquisitions (M&A) as a growth strategy for decades, research has shown indecisive results for common parameters for their execution. The aim of this study is to find out how acquirers identify their resource gaps and close them through acquisitions. The sub-questions of this study focus on finding how resources and capabilities are valued, what is the process through which a company identifies its resource gaps and the need to fill them, and what factors affect the integration of new resources and capabilities. Technological innovation has been acknowledged to be the new driver for M&A deals in the 21stth century. This has made the topic of M&A activity in the technology sector topical and serves as a guideline to narrow this study to concentrate on companies operating in the technology sector. Also, as acquisitions can be experienced differently weather representing the acquirer or the target company, this study was conducted through the acquirer’s point of view. To attain the aim of the study, first a framework was established through existing theories and findings from the academic literature. The conducted framework combined the Resource-Based View and M&A frameworks. Based on the conducted framework and operationalization table, six expert interviews were held to find answers to the chosen research questions. The represented extensive experience in the field of M&A by having represented the acquirer’s management in one or several technology M&A deals. The empirical finding resulted in both findings that supported the previous research as well as some new topics. The most coherent finding was that resources and capabilities are most often bounded to key employees in the companies. At the same time, however, empirical findings of this study conclude that the due diligence process of employees and company-culture is very fragmented and requires more discussion and standardization. In addition, companies experience challenges with communication and employee involvement, as the information of the deal is not often disclosed to wider audience before the very last phase of the pre-M&A phase where the deal is closed. As these employees are bought through an acquisition, it is important to secure their knowledge by careful due diligence process prior to the deal to note the most important findings of the target company, as well as executing appropriate post-integration strategy. By doing this, an acquirer can secure that the bought resources and capabilities are integrated to the new joint company.

Tässä tutkimuksessa tarkastellaan, kuinka ostajat laajentavat resurssejaan ja kyvykkyyksiään teknologiayrityskauppojen avulla. Vaikka yritykset ovat käyttäneet yrityskauppoja kasvustrategiana jo vuosikymmeniä, tutkimukset eivät ole osoittaneet yhteneviä tuloksia yrityskaupan toteuttamisen yleisistä parametreistä. Tämän tutkimuksen tavoitteena on selvittää, kuinka ostajat tunnistavat resurssipuutteitaan ja täydentävät niitä yrityskauppojen avulla. Tutkimuksen alakysymyksissä keskitytään selvittämään miten resursseja ja kykyjä arvostetaan; mikä on prosessi, jolla yritys tunnistaa puutteen resursseissaan ja kyvykkyyksissään ja mitkä tekijät vaikuttavat uusien resurssien ja kykyjen integroimisessa kahden yrityksen välillä. Teknologiainnovaatiot ovat tunnistettu yhdeksi suurimmista motiiveista yrityskaupoille 2000-luvulla. Tämä on nostanut teknologiayrityskaupat ajankohtaiseksi aiheeksi, johon myös tämä tutkimus keskittyy. Tutkimuksen aihe on täten rajattu teknologiasektorilla tapahtuviin yrityskauppoihin. Aiheen rajauksen osalta on myös oleellista huomioida, että yrityskauppa voidaan kokea eri tavalla ostajan ja ostettavan yrityksen välillä. Tämä tutkimus on toteutettu ostajan näkökulmasta. Tutkimuksen tavoitteen saavuttamiseksi luotiin ensin viitekehys olemassa olevien teorioiden ja akateemisesta kirjallisuudesta löydettyjen havaintojen pohjalta. Viitekehys yhdisti resurssipohjaisen teorian sekä yrityskauppateorian oleellisimpia viitekehyksiä. Käytetyn viitekehyksen ja operationalisointitaulukon perusteella toteutettiin kuusi asiantuntijahaastattelua, joilla pyrittiin löytämään vastauksia valittuihin tutkimuskysymyksiin. Jokaisella haastateltavalla oli laajaa kokemusta teknologiayrityskaupoista johtoryhmäasemassa. Tämän tutkimuksen empiiriset löydökset tukevat sekä aiempia tutkimuslöydöksiä, että nostavat esiin uusia näkökulmia. Empiiristen havaintojen perusteella tutkimuksessa todetaan resurssien ja kyvykkyyksien olevan hyvin sidoksissa yrityksen avaintyöntekijöihin. Kuitenkin työntekijöiden ja yrityskulttuurin huolellinen analysointi koetaan hajanaisena, ja aihe vaatisi yleisiä parametrejä. Lisäksi yrityksillä on haasteita viestinnän ja työntekijöiden osallistamisen suhteen, sillä tietoa kaupasta ei tyypillisesti paljasteta laajalle joukolle ennen neuvottelujen päätökseen saattamista. Koska työntekijät ovat tärkeitä resurssi- ja kyvykkyysnäkökulmista, on keskeistä varmistaa heidän keskinäinen yhteensopivuutensa huolellisella analyysilla ennen kauppaa. Tämä nähdään tärkeäksi myös kaupan jälkeisen integraation suunnittelun ja toteutuksen kannalta, jotta ostaja voi edesauttaa ostettujen resurssien ja kyvykkyyksien integrointia uuden yrityksen käyttöön.
Keywords: Mergers and Acquisitions, M&A, Technology, Resources, Capabilities